Potential of Wood Modification Technologies on The Physical and Mechanical Properties of Albizia Falcataria: A Literature Review - Julian, Treza Chandra; Fukuda, Hiroatsu (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Wood modification treatment has grown in popularity over the last few years and continues to expand as an industrial method for improving certain types of wood. As a result of environmental concerns, the wood sector is under more pressure than ever to develop wood alternatives. Nowadays, fast-growing wood species appear to be increasingly potential as substitute wood sources for bridging the supply-demand gap in the wood industry. Albasia (Albizia falcataria), sometimes known as sengon wood, is a fast-growing wood widely planted in Indonesia. However, specific characteristics of the wood, such as low density, low hardness, and low strength, have been hindering its end-use applications as a building material. Therefore, numerous technologies are utilized to enhance wood's physical and mechanical qualities. This paper summarizes the extensive literature on wood modification of Albizia falcataria and synthesizes the major publications on wood properties, chemical changes, wood uses, and quality control. Acetylation, furfurylation, thermal modification, and impregnation as wood modification technologies have been utilized in Albizia falcataria studies. Based on recent investigations, this article aims to review the current state of knowledge regarding the wood modification technologies for improving physical and mechanical properties of Albizia falcataria. Identifying the gaps in research would also aid in accelerating the research activities for deploying these modification technologies on an industrial scale.